A Mössbauer study on iron(II) complex of 2-acetyl-1,3-indandione ⎼ spin-crossover or structural changes - Rusanov, Ventzislav; Ahmedova, Anife; Mitewa, Mariana (European Journal of Chemistry, 2014)
An air stable Fe(II) complex of a cyclic β-triketone, 2-acetyl-1,3-indandione (2AID) was obtained in two different ways and studied by Mössbauer spectroscopy. The Mössbauer data at room temperature point to six-coordinated, high spin Fe(II) complex. The temperature-dependent measurements indicate a phase transition in going from 293 to 77 K. Further lowering the temperature, however, do not cause the expected changes for spin-crossover transition. This data provoked application of quantum chemical methods to determine the origin of the observed appearance of spectral component attributable to low spin Fe(II) complex at 77 K. Based on the results from the theoretical calculations of the Mössbauer parameters of several different geometries and spin states of the Fe complexes of 2AID it was possible to conclude that the obtained Fe(II) complex has a pseudo-octahedral geometry. The experimentally observed temperature-dependence of the Mössbauer spectra is attributed to changes of the axial Fe-O bonds, rather than to spin transition. Discussion is given on the role of the type of the axial ligands for conditioning a spin-crossover process, as suggestion for experimental modelling of novel target materials with desired magnetic properties.